SYNTHESIS OF OPTIMAL STEGANOGRAPHIC METHOD MEETING GIVEN CRITERIA - Vovk, Olesia; Astrahantsev, Andrii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
One of the steganography areas is digital watermarking. In this paper, the technique of comparative analysis of embedding information methods into an image was proposed. A comprehensive analysis of the most relevant steganographic methods of hiding information was made. Own method of embedding information in still images was synthesized. The possibility of studied methods to adapt to the real channels was evaluated for the first time. The robustness and security of steganographic systems based on the proposed method were also demonstrated.